The abundance and origin of cool gas in galaxy clusters in the TNG-Cluster simulation - Staffehl, Milan; Nelson, Dylan; Ayromlou, Mohammadreza; Rohr, Eric; Pillepich, Annalisa (Astronomy and astrophysics, 2025)
In addition to the hot intracluster medium, massive galaxy clusters host complex, multi-phase gaseous halos. In this work, we quantify the abundance, spatial distribution, and origin of the cool (T ≤ 10 4.5 K) gas within clusters. To do so, we combine the TNG-Cluster and TNG300 cosmological magnetohydrodynamical simulations, yielding a sample of 632 simulated galaxy clusters at z = 0 with masses M200c ∼ 10 14−15.4 M⊙. We find that cool gas is present in every cluster at z = 0, although it constitutes only a small fraction of the total gas mass within twice the virial radius, ranging from ∼10 −4 to a few percent. The majority of cool gas resides in the cluster outskirts in infalling satellites and other halos. More rarely, cool gas can also be present in the central regions of clusters. More massive halos contain larger amounts (but not fractions) of cool gas (∼ 10< 10−12 M⊙), and we identified correlations between cluster cool gas fraction and several global halo and galaxy properties at a fixed halo mass. While precise values depend on resolution, these trends remain robust. Using Monte-Carlo Lagrangian tracer particles, we then tracked the origin of cool gas in present-day clusters. We find that the primary source is recent accretion at z ≲ 0.1, predominantly in the form of pre-cooled gas carried by infalling satellite galaxies and other halos. However, in situ cooling of the hot intracluster medium gas accreted at earlier epochs also contributes, especially in present-day cool-core clusters.
Gesehen am 25.02.2026